Poligami Dalam Hukum Kontemporer Implikasi Sosial dan Legal - Anwar, Syaiful; Kesuma Wardani, Rama Wijaya (Hutanasyah : Jurnal Hukum Tata Negara, 2024)
Polygamy, the practice of marrying more than one couple at a time, has been the subject of deep debate in modern society. This article analyzes polygamy from a contemporary legal perspective, focusing on its social and legal implications. We conducted an analysis of legal documents from various jurisdictions and reviewed the relevant literature to understand the legal framework governing polygamy. The results of the study show significant differences in legal approaches to polygamy around the world. Some countries ban it completely, while others allow it with various restrictions. Pro-polygamy arguments often include protections for religious freedom, while counter-arguments highlight gender inequality and the risk of oppression of women in these practices. The social and legal implications of polygamy vary depending on the applicable legal framework. Some families involved in polygamy face challenges in maintaining family stability, feelings of jealousy, and psychological impact on the individuals involved. However, some individuals also feel satisfied with their polygamous lives. In conclusion, polygamy is a complex and diverse issue in contemporary law. The debate about this practice will continue, and more research is needed to understand the deeper impact and consequences of this practice of polygamy on individuals and society. This article provides a better view of this debate and encourages a deeper understanding of the issue of polygamy in modern society.